2018
DOI: 10.1002/jmri.26286
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion Tensor Imaging of the Calf Muscles in Subjects With and Without Diabetes Mellitus

Abstract: 2 Technical Efficacy: Stage 2 J. Magn. Reson. Imaging 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Changes in the water diffusion properties of skeletal muscles have been observed in relation to physiologic changes (age, sex, and exercise) and pathologic changes (ischemia, denervation, trauma, and inflammation) (14,15). DTI studies of skeletal muscle in patients with type 2 diabetes mellitus (DM2) are limited; however, Edalati et al report diffusion differences in plantar flexors when compared with those in healthy participants (16).…”
Section: Key Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in the water diffusion properties of skeletal muscles have been observed in relation to physiologic changes (age, sex, and exercise) and pathologic changes (ischemia, denervation, trauma, and inflammation) (14,15). DTI studies of skeletal muscle in patients with type 2 diabetes mellitus (DM2) are limited; however, Edalati et al report diffusion differences in plantar flexors when compared with those in healthy participants (16).…”
Section: Key Resultsmentioning
confidence: 99%
“…DTI has proven sensitive to reflect muscle alterations in neuromuscular disorders, particularly in Duchenne muscular dystrophy, indicated by higher MD or apparent diffusion coefficients and lower FA values, when compared when compared with healthy participants (10,35). A recent study evaluated the microstructure of plantar flexors of participants with DM2 during isometric contraction and reported a greater elevation in MD from rest to plantar flexion compared with healthy muscles (16). This could indicate that microstructural changes assessed inclusion of participants with DM2 with a more severe degree of neuropathy will enable validation of our results.…”
mentioning
confidence: 99%
“…26,29,[33][34][35][36][37][38] Diffusion-weighted images (DWI) were acquired using a STEAM prototype sequence with an echoplanar imaging (EPI) readout 39 with spectral adiabatic inversion recovery fat suppression: TR/ TE: 6300 ms/42. 4…”
Section: Mr Measurementsmentioning
confidence: 99%
“…There is growing evidence supporting the use of diffusion tensor imaging (DTI) in skeletal muscle. DTI measurements have been shown to be sensitive to muscle changes due to myositis, [1][2][3] diabetes mellitus, 4 muscle injury, 5,6 exercise [7][8][9] and ageing. 10 The majority of these studies use spin echo DTI; however there are advantages in using a stimulated echo acquisition mode (STEAM) approach.…”
Section: Introductionmentioning
confidence: 99%
“…It can be speculated that a decrease in VI muscle activity due to IMAT might be compensated by an increase in VL muscle activity. Some studies showed that higher λ 1–3 values were observed in nonathletes (vs. athletes), 24 females (vs. males), 8 and people with diabetes mellitus (vs. healthy people), 25 from which we speculate that the higher λ 1–3 values may be caused by larger percentages of IMAT. However, the present study showed that the QM IMAT percentage had no statistically significant relationships with any water diffusivities, whereas the infiltration direction of the IMAT differed in the individual QMs, and the relationships between IMAT and the water diffusivities were strongest in the VM.…”
Section: Discussionmentioning
confidence: 62%